Инновационные процессы в современной педагогике - Шевченко, Л.Я.; Назарова, С.В. (My University, 2016)
Innovative pedagogy requires a rethinking of the whole educational process, both training and education. According to the authors, classical pedagogical theory is hopelessly outdated, building on her upbringing of current generations should not be in the new environment. The article refers to the emerging new science, whose main task is to change and reorganization of the entire educational system on the basis of innovation. The authors conclude on the need to transform all kinds of activities, including training, educational, administrative, research and development.
Keywords: Pedagogy; Innovation; education; resources; the paradigm of efficiency